Coral Fishes of Chaetodontidae in North Salawaty and South Batanta Districts, Raja Ampat Regency, West Papua Province - Ari B. Rondonuwu; Lawrence J. L. Lumingas; Nego E. Bataragoa (Jurnal Ilmiah PLATAX, 2017)
The objective of this study was to examine the general condition of Chaetodontidae fish in North Salawati and South Batanta Districts, i.e. species composition and number of species, abundance and density of individuals, as well as ecological indices.  Data were collected by using Visual Census method with a 70 m-transect, width 2.5 m to the left and 2.5 m to the right. Therefore, the total area observed was 350 m2. This study found 6 (six) genera with 32 species and total abundance of 791 individuals, Chaetodon, Chelmon, Coradion, Heniochus, Hemitaurichthys and Forcipiger.  Based on number of species, the studied area had highly diverse coral fish species.  Chaetodon lunulatus and C. kleinii were the most species found with the highest number of individuals. Station KBS01 had highest number of species and individual abundance. Diversity index was 2 < H’ < 3 meaning that the coral fish communities in both districts were stable.Keywords : Coral Fishes, Chaetodontidae, Raja Ampat Island. Abstrak Tujuan penelitian ini secara umum adalah untuk mengkaji kondisi existing ikan karang famili chaetodontidae di Kecamatan Salawati Utara dan Kecamatan Batanta Selatan, yaitu komposisi dan jumlah spesies, kelimpahan individu, dan indeks ekologi. Pengambilan data dilakukan menggunakan metode Sensus Visual dengan panjang garis transek 70 m, lebar pengamatan 2,5 meter ke kiri dan 2,5 meter ke kanan.  Dengan demikian, luas areal pengamatan adalah 350 m2. Penelitian ini menemukan  6 (enam) genera dengan 32 spesies dan kelimpahan individu total 791 individu terdiri dari Chaetodon, Chelmon, Coradion, Heniochus, Hemitaurichthys dan Forcipiger dengan 32 spesies. Oleh Karena itu, wilayah ini  memiliki keanekaragaman jenis ikan karang yang tinggi dimana Chaetodon lunulatus dan C. kleinii  paling sering ditemukan dengan jumlah individu tertinggi.   Stasiun KBS01 memiliki jumlah spesies dan kelimpahan individu tertinggi. Nilai indeks keanekaragaman berada pada kisaran    2 < H’< 3 yang berarti bahwa komunitas ikan karang di kecamatan ini  dinyatakan stabil.